The development, design and characterisation of a scale model Horizontal Axis Tidal Turbine for dynamic load quantification. (August 2020) - Allmark, Matthew; Ellis, Robert; Lloyd, Catherine; Ordonez-Sanchez, Stephanie; Johannesen, Kate; Byrne, Carl; Johnstone, Cameron; O'Doherty, Tim; Mason-Jones, Allan
Abstract: The paper describes the development and characterisation of three 0.9 m diameter lab-scale Horizontal Axis Tidal Turbines. The blade development process has been outlined and was used to generate a design specification. Each turbine houses instrumentation to measure rotor thrust, torque and blade root bending moments on each blade, in both 'flapwise' and 'edgewise' directions. A permanent magnet synchronous machine and encoder are integrated to allow for servo-control of the turbine as well as to provide position and rotational velocity measurements, resulting in three turbines that can be individually controlled using speed or torque control. Analogue signals are captured via a real-time operating system and field programmable gate array hardware architecture facilitating sample rates of up to 2 kHz. Results from testing the pilot turbine at three differing facilities during the development process are presented. Here good agreement, less than 7 % variation, was found when comparing the testing undertaken at various flume and tow tank facilities. Lastly, the findings of a test campaign to characterise the performance of each of the three turbines are presented. Very good agreement in non-dimensional values for each of the three manufactured turbines was found. Highlights: Outlines the development of three 1/20th scale horizontal axis tidal turbines. Presents the blade development undertaken to create an optimum turbine rotor. Details of the drivetrain, instruments and control systems design are given. Tests at differing facilities and the same facility for similar devices presented. The paper discusses aspects of good practice for flume/tow-tank testing.